A Systems Thinking Approach to Analysis of the Patient Protection and Affordable Care Act. (January 2015) - Williams, John C.
Abstract : The public health community is challenged with understanding the many complexities presented by systems thinking and its applications in systems modeling. The model presented encompasses multiple variables needed (eg, model building) for the construction of a conceptual system model of the Patient Protection and Affordable Care Act (ACA). The model tracks the ACA from inception, through passage, March 2010, to its current state. Justification for the need to reform the current health care system rests, in part, on the heels of social justice. Proponents of the ACA have long argued that health reform was needed by the millions of uninsured person who suffered from health disparities, took little advantage of health prevention advice, and faced issues of access to providers as well as insurers. In addition the ACA seeks to address our uncontrollable spending on health care delivery. This article highlights the ACA from a systems perspective. The conceptual model presented encompasses both health reform variables (eg, health care provisions, key legislative components, system environment) and system variables (eg, inputs, outputs, feedback, and throughput) needed to understand current health care reform efforts from a systems perspective. The model presented shows how the interrelationships and interconnections of elements of a system come together to achieve its purpose or goal.